Basic oculomotor function is similar in young children with ASD and typically developing controls. Issue 12 (18th August 2021) - Avni, Inbar; Meiri, Gal; Michaelovski, Analya; Menashe, Idan; Shmuelof, Lior; Dinstein, Ilan
Abstract: A variety of eye tracking studies have demonstrated that young children with ASD gaze at images and movies of social interactions differently than typically developing children. These findings have supported the hypothesis that gaze behavior differences are generated by a weaker preference for social stimuli in ASD children. The hypothesis assumes that gaze differences are not caused by abnormalities in oculomotor function including saccade frequency and kinematics. Previous studies of oculomotor function have mostly been performed with school‐age children, adolescents, and adults using visual search, anti‐saccade, and gap saccade tasks that are less suitable for young pre‐school children. Here, we examined oculomotor function in 144 children (90 with ASD and 54 controls), 1–10‐years‐old, as they watched two animated movies interleaved with the presentation of multiple salient stimuli that elicited saccades‐to‐targets. The results revealed that the number of fixations, fixation duration, number of saccades, saccade duration, saccade accuracy, and saccade latency did not differ significantly across groups. Minor initial differences in saccade peak velocity were not supported by analysis with a linear mixed model. These findings suggest that most children with ASD exhibit similar oculomotor function to that of controls, when performing saccades‐to‐targets or freely viewing child‐friendly movies. This suggests that previously reported gaze abnormalities in children with ASD are not due to underlying oculomotor deficiencies. Lay Summary: This study demonstrates that children with ASD perform similar eye movements to those of controls when freely observing movies or making eye movements to targets. Similar results were apparent across groups in the number of eye movements, their accuracy, duration, and other measures that assess eye movement control. These findings are important for interpreting previously reported differences in gaze behavior of children with ASD, which are likely due to atypical social preferences rather than impaired control of eye movements.